Exploring Potentials for Bioresource and Bioenergy Recovery from Vinasse, the “New” Protagonist in Brazilian Sugarcane Biorefineries - Fuess, Lucas T.; Lens, Piet N. L.; Garcia, Marcelo L. [UNESP]; Zaiat, Marcelo (MDPI, 2022)
Vinasse management in biorefineries bears a burden for sugarcane industries. Despite its high potassium-related fertilizer potential, a series of negative environmental impacts is expected to occur in long-term soil applications of vinasse through fertirrigation. Conversely, a high biodegradable organic content characterizes vinasse as a potential substrate for bioresource and bioenergy recovery from numerous (bio)technological perspectives. This review presents the alternative approaches proposed for sugarcane vinasse management in Brazil, with special attention dedicated to the role of anaerobic digestion as the core conversion step. The suitability of applying phase separation, i.e., the separation of fermentation from methanogenesis in sequential reactors, is discussed in detail. Laboratory and full-scale experiences were considered to discuss the energetic potential of sugarcane vinasse through biogas generation. With a national installed capacity of up to 1603 MW, energy from vinasse could replace half of the coal-derived electricity in Brazil. Meanwhile, investing in vinasse fermentation to obtain soluble organic metabolites could provide more than 10 g L−1 of (iso)butyrate. This is the first review addressing the potential use of sugarcane vinasse in anaerobic biorefineries that discusses applications far beyond conventional biogas production, and encourages the rational use of vinasse as a raw material for bioprocesses, either in short- or long-term scenarios.
Keywords: biodigestion; bioenergy recovery; bioresource production; sugarcane biorefinery; two-phase systems; vinasse management/exploitation